Reframing Human Rights: Addressing Food Insecurity in a Global Context .......... 135 - Podolska, Anna; Śniadach, Olga (Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies, 2025)
The purpose of this chapter is to draw attention to the flawed perception of the right to food solely from the perspective of a social right, whereas it is inextricably linked to other human rights. The right to food is very often cited as exemplifying the weakness of human rights. It illustrates a situation in which there is a perceptible inconsistency between the rights on one side and the obligations on the other. The right to food is not unattainable, but it is unfortunately unrealised. Food is the most basic human need, the lack of food security has negative effects on all other levels: economic, social and political. In the past, problems related to food provision were local in nature, nowadays, in a globalising world, the food problem has become a global problem. Global problems are interlinked. Human rights, in their universality, contain prerogatives that are vested in everyone. The addressee of these rights is the state and, increasingly as of late, the international community.